Autour de la pensée raciale et raciste en Italie (1850-1945) - Aurélien Aramini; Elena Bovo (Cahiers d’histoire.)
This article identifies three key moments in the racial thought formulation in Italy from the mid-nineteenth century to the fascist double decade. The first moment corresponds to the introduction of the Aryan myth in the peninsula, when Indo-European philology provided the scientific grounds to buttress an anticlerical campaign, synonymous with cultural and literary progress. The second moment arrived with the birth of criminal anthropology in the last third of the nineteenth century. In the wake of Cesare Lombroso, a singular racial thought developed in Italy which reconceptualised the north-south social and economic divide of the recently unified Italy in physical, biological and psychological terms. The last moment constitutes a break with criminal anthropology. Fascism, which rejected the Italy’s internal north-south racial fracture and redirected the vector of racist stigmatization from the inside out, namely from the "southern" to the "Jewish" or "colonized".